Perspective Of Public Choise In Institution Political Economy - Noor, Munawar (Advances in Social Sciences Research Journal, 2018)
The dichotomy between economics and politics has been so long that both are incapable of giving the same conclusions about the object being studied. Economics only examines the institutional aspects of the market without touching the non-market social institutions. The basis of market institutions to see the economic phenomenon while based on politics is very poor analytical framework. The perspective of public choice as a link that can provide a framework of analysis based on market phenomena. This allows the re-enactment of economic and political fields within a region. Analysis of the close relationship between economics and politics can be studied from the historical aspect, the collaboration between economics and politics, and the achievement of state goals, the cooperation among experts in each field, the analysis of national development, the condition of a country. Thus found a new phenomenon that connects the two that cannot be captured perfectly by both groups.